Effect of proofing profile on bread texture and microstructure previous to freezing process; a correlation with sensory attributes - Fabregat, Nieves (2015)
Within the bakery industry, as well as in all other industries, product development is an important area of research. The freezing process and its effects on the final bread have been studied over the last decades. The main objective of the present study was to verify if bread that has been fully proofed as dough prior to the freezing process has the same quality as bread from doughs that were non-proofed, or partly proofed before freezing, as well as to find out how pre-fermentation affects the porosity and texture of the final bread. Two kinds of bread dough (sweet and rye) mixed in an industrial bakery were proofed at three different profiles (non-proofed, half-proofed and fully proofed), then frozen and stored 2.5 months at a temperature of -20°C. The dough microstructure was studied with a confocal laser scanning microscopy and a computed tomography method. The volume, texture, final appearance and consumer acceptance of the final baked buns were all evaluated. The results showed that, in the final appearance, the volume of the bread containing rye flour at different proofing profiles was more similar to the volume of the reference sample, which was the non-proofed dough before freezing, than the volume of the sweet breads was. Sweet dough that had been half and fully proofed resulted in a lower volume, even after optimizing the process. Despite the similarities between the buns containing rye flour, a significant difference was also observed between them in the product profile obtained from the sensory analyses, in addition to the specific volume and the compressive stress. Product profiles for the different proofing profiles differed in almost all the tested attributes except in elasticity and flavor. Consumers were also able to distinguish between the products. Sweet dough showed an uneven gluten network that was not well developed and in some of the dough types showed agglutinated fat. Using 3D-micro-CT images, it was possible to observe some differences in density and areas with no pores. This study reveals that some achievements have been accomplished with regards to savory bread, but there is still a need for more research to be carried out on sweet bread as well as to develop a process in which a final proofing could be avoided in today’s bread industry. The bread baked from dough that was frozen and stored long-term, 4.5 months at -20°C, showed a noticeable volume reduction. Prolonged proofing time was not enough to compensate and obtain a higher volume.